Tap the blue circles to see an explanation.
$$ \begin{aligned}(r-h)^3& \xlongequal{ \color{blue}{ \text{\normalsize{ \htmlClass{explanationCircle explanationCircle1}{\textcircled {1}} } }}}r^3-3hr^2+3h^2r-h^3 \xlongequal{ } \\[1 em] & \xlongequal{ \color{blue}{ \text{\normalsize{ \htmlClass{explanationCircle explanationCircle2}{\textcircled {2}} } }}}-h^3+3h^2r-3hr^2+r^3\end{aligned} $$ | |
① | Find $ \left(r-h\right)^3 $ using formula $$ (A - B) = A^3 - 3A^2B + 3AB^2 - B^3 $$where $ A = r $ and $ B = h $. $$ \left(r-h\right)^3 = r^3-3 \cdot r^2 \cdot h + 3 \cdot r \cdot h^2-h^3 = r^3-3hr^2+3h^2r-h^3 $$ |
② | Combine like terms: $$ -h^3+3h^2r-3hr^2+r^3 = -h^3+3h^2r-3hr^2+r^3 $$ |